2012
DOI: 10.1074/jbc.m111.333450
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 and FUS RNA-binding Proteins Bind Distinct Sets of Cytoplasmic Messenger RNAs and Differently Regulate Their Post-transcriptional Fate in Motoneuron-like Cells

Abstract: Background:The RNA-binding proteins TDP-43 and FUS form abnormal aggregates in patients with amyotrophic lateral sclerosis and frontotemporal lobar dementia. Results: We identified the mRNAs associated to these proteins in the cytoplasm of NSC-34 cells. Conclusion: TDP-43 and FUS recognize distinct transcripts and differently regulate their fate. Significance: Our results clarify TDP-43 and FUS role in neuronal metabolism and neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
255
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(270 citation statements)
references
References 66 publications
(71 reference statements)
15
255
0
Order By: Relevance
“…16 Several global scale analyses based on RIP-seq and CLIP-seq have been performed to identified TDP-43 mRNA targets in neuronal, non-neuronal cells, mouse brain, healthy and diseased human brain tissues. [8][9][10][11]30 These studies showed that the most significantly enriched pentamer-binding sites were GUGUG and UGUGU, confirming previous in vitro data. 7,37 Add2 brain specific PAS DSE contains 4 GU repeats in its sequence (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…16 Several global scale analyses based on RIP-seq and CLIP-seq have been performed to identified TDP-43 mRNA targets in neuronal, non-neuronal cells, mouse brain, healthy and diseased human brain tissues. [8][9][10][11]30 These studies showed that the most significantly enriched pentamer-binding sites were GUGUG and UGUGU, confirming previous in vitro data. 7,37 Add2 brain specific PAS DSE contains 4 GU repeats in its sequence (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…[29][30][31] The observation that the TDP-43 modulation of Add2 expression levels was detected in both the endogenous transcript and minigene derived mRNAs, which contains only the PAS and their respective 3 0 UTR flanking regions of Add2, and in minigene constructs in which the Add2 DSE was replaced by DSE sequences that do not contain GU repeats (Fig. 4A), further supported the possibility that TDP-43 could influence Add2 mRNA half-life through the binding to the 3 0 UTR.…”
Section: Downregulation Of Tdp-43 Results In a Reduction Of Add2 Mrnamentioning
confidence: 99%
See 2 more Smart Citations
“…Still, genes displaying overlapping patterns of dysregulation represented only a small fraction of the total, with the majority of differentially expressed genes being distinct in each case [36]. In addition, targeted reduction in TDP43 or FUS produced disparate effects in NSC34 mouse motor neuron-like cells [62]. In an animal model of ALS, the overexpression of FUS bearing an ALS-associated mutation (R521C) significantly affected the expression of >700 genes [63].…”
Section: Rna Expressionmentioning
confidence: 99%